Model Perencanaan Strategis Dalam Service Organization : Sebuah Kajian Literatur - , Rakhmiana; Imelda, Johanna Debora (UI Scholars Hub, 2023)
In Indonesia, several types of HSOs include government organizations, private organizations, and non-profit organizations. Strategic planning is crucial for HSOs as it helps them to map their direction and goals, manage their resources, identify opportunities and challenges, coordinate their activities, and measure and evaluate their performance. To assist in strategic planning, various mapping models can be used. One of the models that can be used is Scenario- Based Road Mapping (SBRM). This research is a literature review that discusses different strategic planning models for HSOs, which can help organizations formulate more effective and adaptive strategies. These models can help HSOs better understand how strategic planning models such as SBRM, Balanced Scorecard, and ERM can be applied in an organizational context. This research aims to examine these various models, identify their strengths and weaknesses, and provide deeper insights into strategic planning models in HSO. Strategic planning is a crucial aspect of HSO safety and survival, and with a better understanding of various mapping models, organizations can better meet challenges and achieve their goals. It is important for HSOs to recognize the significance of good strategic planning. Therefore, strategic planning must be carried out by professional individuals who have a deep understanding of strategic design creation and sensitivity to changes and threats.